PREDIKSI JUMLAH PRODUKSI KOPRA MENGGUNAKAN METODE REGRESI LINEAR BERGANDA PADA UMKM MANDIRI DESA LION: Indonesia - ABDUL_MUHRIZAL_ZULKIFLI_H_MARADA; Haditsah Annur; Yunus, Warid; Panna, sudirman S. (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2025)
Abstract This study aims to apply multiple linear regression methods in predicting copra total production at CV. Lion Utama. The results of system testing show that the value of V(G) = CC = 2 indicates that the system meets the requirements of programming logic and is not complex. Black-Box Testing also shows that the system is free of component errors. The prediction of copra total production for January 2022 using the multiple linear regression method gives valid results. The accuracy of this prediction is measured by Mean Absolute Percentage Error (MAPE), resulting in a value of 77.27%, indicating a Fairly High level of accuracy in copra production estimation. Keywords: production prediction, copra, multiple linear regression, CV. Lion Utama, MAPE